Analysis Of Plant Diversity Agroforestry In The Mount Lawu Natural Forest Area - Susanto, Anang; Julissa Ek-Ramos, Maria (CV. Inara, 2024)
The natural forest area of Mount Lawu, with various plant compositions, can be landscaped by humans to produce diverse landscape characters in the natural forest area. The solution for implementing the Agroforestry system is very appropriate because land management with this system is to overcome problems arising from changes in land use and soil and water conservation. The research aims to analyze plant diversity in agroforestry practices with services in natural landscape water conservation and develop strategies in agroforestry services. This research was carried out on the natural forest of Mount Lawu, using the fast AgroBiodiversity Appraisal method. The research results show that the composition of the vegetation structure at the research location varies greatly with a high agroforestry diversity index. The practice of agroforestry in the natural forest of Mount Lawu at an altitude of 1600 above sea level with the highest important index value is dominated by the plant species Arenga pinnata, pine merkusi, and paraserientes falcataria. In the slope area of 2200 meters above sea level, the plant species are dominated by Acacia decurrens, while at an altitude of 2800 meters above sea level, the plant species are dominated by Fuchsia magellanica, Anaphalis javanica, Casuarina junghuniana.